Sistem Pendukung Keputusan Beasiswa Diklat dengan Fuzzy Multiple Attribute Decission Making (MADM) - Tri Handayani, Wawan Laksito Yuly Saptomo, Teguh Susyanto (STMIK Sinar Nusantara, 2013)
The scholarship is to assist students in taking their studies. The process of building decision support system using the method of training scholarships Fuzzy MADM (Multiple Attribute Making Decission) Simple Addictive Weighting method (SAW). Fuzzy MADM is used to find an alternative from a number of alternatives with certain criteria. Research carried out by finding the weights for each attribute, then performed to determine the process of ranking the alternatives given. This research method is done through observation, interviews, documentation and literature. The system design is made with Contex Diagrams, HIPO, DFD, ERD, relations between tables and database design. The process of determining scholarship with Fuzzy MADM can speed up the process of ranking, reduce errors determining scholarship recipients, and help the team selectors in determining scholarship recipients. Keywords: Scholarship, Fuzzy MADM, SAW, Criteria.